Connecting working and long-term memory: Bayesian-hierarchical multinomial model-based analyses reveal storage next to retrieval differences. - Streitberger, Carolin; Kuhlmann, Beatrice G.; Meier, Matt E.; Arnold, Nina R. (Memory & Cognition, 2024)
Individual differences in working memory capacity (WMC) are correlated with long-term memory (LTM) differences. Whether this is because high-WMC individuals encode more effectively, resulting in better LTM storage, or because they better retrieve information from LTM is debated. In two experiments, we used Bayesian-hierarchical multinomial modeling to correlate participant-level storage and retrieval processes from LTM recall to WMC abilities estimated from operation and symmetry complex span tasks. In Experiment 1, we presented participants with 20 consecutive words, including semantically associated pairs (e.g., knife and fork), to assess LTM processes. Participants received standard (n = 242) or associative-storage instructions (n = 222) and then completed a free recall task. In Experiment 2, we instructed participants (N = 239) to memorize 40 cue-target words as pairs before completing free and cued recall tasks. Correlations with WMC emerged with storage and retrieval processes and only when an associative storage strategy was instructed (Experiment 1). When associative processing was inherent to the task (Experiment 2), only the associative storage, not the retrieval advantage, replicated. The strategy reports suggest that high-WMC individuals use associative encoding strategies more effectively, resulting in better storage in LTM.